Recovery of antioxidant from Decapterus Macarellus waste using wet rendering method - Nurlaylatul Akmal, Mohd Yusoh; Rohaida, Che Man; Nurul Aini, Mohd Azman; Shalyda, Md Shaarani; Siti Kholijah, Abdul Mudalip; Siti Zubaidah, Sulaiman; Zatul Iffah, Mohd Arshad (Elsevier Ltd, 2022)
In Malaysia, Decapterus Maruadsi is widely used as the main ingredient in food products such as ‘keropok lekor’ and fish cracker. The wastes generated from the fish snack industry are underutilized and most are discarded into the sea, generating considerable environmental pollution. The recovery of antioxidants in the fish wastes could lead to the development of a very exciting and promising alternative source of commercial antioxidant compounds. The objective of the present work is to investigate the effect of temperature, type of solvent, extraction time, and ratio of sample to solvent loading in the extraction of antioxidants from Decapterus Maruadsi waste using the wet rendering method. The collected fish waste of Decapterus Maruadsi was pre-treated and then subjected to a wet rendering treatment at 0–60 °C for 30–150 min with ratio of sample to solvent loading of between 1:10 and 9:10 (w/v). The presence of antioxidant in the extract was analyzed using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and Total Phenolic Compound (TPC) assays. Based on the results of this study, wet rendering treatment performed for 90 min at 30 °C with a ratio of sample to solvent loading of 3:10 produced an extract with the highest concentration of active antioxidant compounds. Besides, only N-Acetyl-glutamic acid was identified with LCMS QTOF analysis. These results suggest that the fish waste of Decapterus Maruadsi can be exploited to become a source of antioxidants for food and pharmaceutical applications.